Synectic Learning Model to Improving Santri's Cognitive Ability in Balaghah Learning - Muhammad Afthon Ulin Nuha; Miftahul Mufid; Mas Tajuddin Ahmad; Nurul Musyafaah (IAIN Madura, 2023)
Balaghah learning is one of the Arabic language learning families that Arabic learners must understand and learn. The learning process of Balaghah at the An-Najiyah Bahrul Ulum Jombang Islamic Boarding School, which is still monotonous, affects the low thinking ability of students and the results of cognitive abilities. Therefore, to prepare individuals with creative thinking skills in solving problems, efforts are needed to make it happen, one of which is using a synectic learning model. The purpose of this study was to: (1) find out the results of the cognitive abilities of Balaghah learning before the synectic learning model was applied to the students of the An-Najiyah Islamic Boarding School Bahrul Ulum Jombang, (2) find out the results of the cognitive abilities of Balaghah learning after applying the synectic learning model to the students of the An-Najiyah Islamic Boarding School -Najiyah Bahrul Ulum Jombang, (3) knowing the results of evaluating the use of synectic learning models in Balaghah learning on the cognitive abilities of the students of An-Najiyah Bahrul Ulum Jombang Islamic Boarding School. This research is quantitative research with a quasi-experimental approach. The research design used the Pretest-Posttest Control Group Design. The sampling technique is Probability Sampling and how to determine the sample by random cluster sampling. Data collection techniques using test instruments and documentation. The instrument's validity uses content validity with the results of the data being declared valid—instrument reliability using the alpha cronbach technique. Data analysis used descriptive analysis. The prerequisite test uses the normality test and homogeneity test. Test the hypothesis using the T-test. The results showed that: (1) the pre-test results for the control class obtained an average of 36.4, with the highest score of 60 and the lowest score of 20. Meanwhile, the average pre-test for the experimental class was 36, with the highest score of 60 and the lowest score of 20. (2) ) the average post-test result for the control class was 66.4, with the highest score being 90 and the lowest score being 30. Meanwhile, the average post-test in the experimental class was 79.2, with the highest score being 100 and the lowest being 40. (3) there was an influence of the learning model synectic on the cognitive abilities of Balaghah learning in An-Najiyah Bahrul Ulum Jombang Islamic Boarding School students. Based on the results of the t-test, namely 0.887 < 1.994 or t count < t table on the post-test results of the experimental and control classes. This shows that the synectic learning model affects the cognitive abilities of students.